2013
DOI: 10.1111/jfd.12074
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and residue depletion of erythromycin in rainbow trout Oncorhynchus mykiss (Walbaum)

Abstract: Erythromycin (ERY) is a drug active against Gram-positive bacteria such as Lactococcus garvieae, a pathogen responsible for an important disease that may cause a substantial decrease in rainbow trout Oncorhynchus mykiss (Walbaum) production, the species of fish most commonly produced in Italy. In the literature, studies on the kinetics behaviour of ERY in fish are limited. Therefore, the aim of the present study was to evaluate the pharmacokinetics of ERY in rainbow trout after a single oral treatment with 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Only partial information of PK and tissue distribution of oxytetracycline, oxolinic acid and sulfadimidine (sulfamethazine) are available so far (Chai‐anan et al, 1993; Chen et al, 2020); PK and tissue depletion characteristics of FF, one of the most popularly used antimicrobials in fish farming, has yet to be evaluated in this fish. The current study found that the serum concentration‐time profile of FF in Asian seabass after administration via medicated feed was best fitted with the one‐compartmental model, which is in line with the general observation that a drug following medicated feed administration is usually best described by the one‐compartmental model (Chen et al, 2005; Di Salvo et al, 2013; Ibrahim et al, 2019; Teles et al, 2016), whereas those after oral gavage of drug solution often best explained by the two‐compartmental model (Hu et al, 2013; Koc et al, 2009; Rairat et al, 2020; Rairat, Liu, et al, 2022; Shan et al, 2020; Zhang & Li, 2007). Following voluntary ingestion of the medicated feed over a certain period of time (usually within a few minutes), drug particle/molecules on the surface of the pelleted feed take time to be released before being absorbed through the fish intestinal epithelium and appearing in the systemic circulation.…”
Section: Discussionsupporting
confidence: 88%
“…Only partial information of PK and tissue distribution of oxytetracycline, oxolinic acid and sulfadimidine (sulfamethazine) are available so far (Chai‐anan et al, 1993; Chen et al, 2020); PK and tissue depletion characteristics of FF, one of the most popularly used antimicrobials in fish farming, has yet to be evaluated in this fish. The current study found that the serum concentration‐time profile of FF in Asian seabass after administration via medicated feed was best fitted with the one‐compartmental model, which is in line with the general observation that a drug following medicated feed administration is usually best described by the one‐compartmental model (Chen et al, 2005; Di Salvo et al, 2013; Ibrahim et al, 2019; Teles et al, 2016), whereas those after oral gavage of drug solution often best explained by the two‐compartmental model (Hu et al, 2013; Koc et al, 2009; Rairat et al, 2020; Rairat, Liu, et al, 2022; Shan et al, 2020; Zhang & Li, 2007). Following voluntary ingestion of the medicated feed over a certain period of time (usually within a few minutes), drug particle/molecules on the surface of the pelleted feed take time to be released before being absorbed through the fish intestinal epithelium and appearing in the systemic circulation.…”
Section: Discussionsupporting
confidence: 88%